Crystallization, preliminary X-ray analysis and Patterson search of a new aspartic protease isolated from human urine - Canduri, F.; Teodoro, LGVL; Lorenzi, CCB; Gomes, RAS; Fontes, MRM; Arni, R. K.; de Azevedo, W. F. (Academic Press Aust, 1998)
Aspartic protease (EC 3.4.23) make up a widely distributed class of enzymes in animals, plants, microbes and, viruses. In animals these enzymes perform diverse functions, which range from digestion of food proteins to very specific regulatory roles. In contrast the information about the well-characterized aspartic proteases, very little is known about the corresponding enzyme in urine. A new aspartic protease isolated from human urine has been crystallized and X-ray diffraction data collected to 2.45 Angstrom resolution using a synchrotron radiation source. Crystals belong to the space group P2(1)2(1)2(1) the cell parameters obtained were a=50.99, b=75.56 and c=89.90 Angstrom. Preliminary analysis revealed the presence of one molecule in the asymmetric unit. The structure was determined using the molecular replacement technique and is currently being refined using simulated annealing and conjugate gradient protocols.
Keywords: aspartic protease; Crystallography; drug design; synchrotron; X-ray analysis